Lepton physics at CERN and Frascati - Cabibbo, N. (World Scientific series in 20th century physics ;, 1994)
This reprint volume is in honour of one of the leaders of Italian high-energy physics, Antonino Zichichi, who is now 65 years old. It covers the first part of his activity: the years 1959-1976, probably the most intense of his scientific career. The volume includes reprints of articles and of some published laboratory reports, documenting the extraordinary constancy of Zichichi in a scientific programme which spanned more than a decade and laid the foundations for the subsequent discovery by M. Perl of the heavy lepton, HL (now called]symbol]), first proposed and searched for at CERN and Frascati by Zichichi in the early sixties.